Analisis Faktor-Faktor Yang Memengaruhi Foreign Direct Investment Tingkat Provinsi di Indonesia - Nyamando, Yasidik; Thomas Andrian (Goodwood Publishing, 2025)
This study aims to analyze the factors that influence the analysis of factors that influence foreign direct investment at the provincial level in Indonesia. The data used is panel data from 34 provinces in Indonesia during the period 2014-2023. The analysis method used is dynamic panel data regression with the Generalized Method of Moment approach, using the variables of gross regional domestic product per capita, inflation, human development index, provincial minimum wage, ICT development index, road length, and FDI in the previous year. The results showed that the variables of gross regional domestic product per capita, inflation, road length, and FDI in the previous year had a positive and significant effect on foreign direct investment, while the provincial minimum wage had a negative and significant effect on foreign direct investment. However, the variables of human development index and ICT development index have no significant effect on foreign direct investment.